READING PSALM 78 MULTIDIMENSIONALLY: THE AUTHORIAL DIMENSION - Kim, Yeolib (Scriptura, 2003)
This article is part of an attempt to read Psalm 78 multidimensionally. It is the second in a proposed series of three articles.2 The articles deal with the dimension of the author, as part of the multi-dimensional reading. It deals with the heading of the Psalm, íhe redaction history of the Psalm, its dating and historical setting and its canonical shape. The Sitz im Leben of the psalm is the recitation of the psalm in the Jerusalem temple by a (Levitical) priest, when there was an attempt to unite the worship of the North and the South during the divided monarchy (922-587 B.C.). The traditions of wisdom, covenant-Torah, guidance, wilderness, Exodus, and conquest are united in Psalm 78, forming a new welded tradition which stresses the importance of remembrance with regard to the survival of the ancient traditions. Psalm 78 can be seen as an example of God’s response to íhe questions and complaints from the adjacent psalms and other psalms in Book III of the Psalter. In this regard, Psalm 78 is not a mere report of Israel’s failure, but of the triumph of Yahweh’s covenantal faithfulness which creates a new beginning for the people of God.